The spectrum of giant cell arteritis and polymyalgia rheumatica: revisiting the concept of the disease - Dejaco, Christian; Duftner, Christina; Buttgereit, Frank; Matteson, Eric L.; Dasgupta, Bhaskar (Rheumatology (Oxford, England), 2017)
GCA and PMR are conditions of older persons that frequently overlap. The traditional concept of GCA has focused on cranial symptoms such as headache and visual disturbance, but extra-cranial manifestations such as constitutional symptoms, polymyalgia and limb claudication have also long been recognized. These symptoms may coincide with cranial GCA, occur as an independent clinical subset [large-vessel (LV) GCA] or overlap with PMR. Imaging studies have demonstrated that up to one-third of patients with PMR have subclinical LV inflammation at disease outset. The implication of this finding for PMR management is unclear. Pathophysiological studies have emphasized the pivotal role of dendritic cells (DCs) and T cells in the pathogenesis of GCA, and the activation of certain pattern recognition receptors on DCs may determine the clinical subset of GCA. In patients with only PMR clinically, it is conceivable that transmural arterial inflammation has either not yet started or is prevented by unexplored regulatory pathways. This concept is supported by vasculitis of peri-adventitial small-vessels and activated DCs in the adventitia of temporal arteries, in the absence of media-infiltrating T cells. This review examines the clinical and pathophysiological spectrum of GCA and its subsets with PMR, the role of newer imaging techniques for GCA diagnosis and the management of these diseases.